Jordanian Folkloric Songs in Translation: Mousa’s Song They Have Passed by Without a Company as a Case Study - Al-Azzam, Bakri; Al-Kharabsheh, Aladdin (Meta)

(untitled) (Les Presses de l’Université de Montréal, 2011)
Folkloric song-translation is a research area that diverges acutely from the centre of interest of interlingual-intercultural transfer in general, and Arabic-English translation studies in particular. This paper attempts to shed light into Abdu Mousa’s culture-bound song marren wa ma ma’hin hada (they have passed by without a company), as an instance of the challenges that folkloric songs may pose in translation, and how, when translating between cultures with different discursive properties, the translator has a certain leeway when reformulating the lingual-cultural import of the source text for target readers. Drawing on Low’s (2005a) Pentathlon Approach, and placing a strong emphasis on content, the study highlights the problems and difficulties involved in translating this type of song, and demonstrates a number of unique aspects of translating folkloric songs, which involve elements of sense, naturalness, cultural references, and how these elements are interconnected and entangled with each other. These insurmountable difficulties are accounted for by the existing sharp linguistic and cultural differences between Arabic and English, and, the incompatibilities between the two working concept systems of the two languages, which add to the intricacy of translating this type of literature. On a less formal level, colloquialism has been found to have had its way to the source language text, a factor which further complicates the abridgement process.